2018
DOI: 10.1016/j.ajog.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Infection-induced thrombin production: a potential novel mechanism for preterm premature rupture of membranes (PPROM)

Abstract: Background Preterm premature rupture of membranes (PPROM) is a leading contributor to maternal and neonatal morbidity and mortality. Epidemiologic and experimental studies have demonstrated that thrombin causes fetal membrane weakening and subsequently PPROM. Although blood is suspected as the likely source of thrombin in fetal membranes and amniotic fluid of patients with PPROM, this has not been proven. Ureaplasma Parvum (U. parvum) is emerging as a pathogen involved in prematurity, including PPROM, but unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…All of the metabolite changes discussed above may work together to impair the healthy vaginal microecology and lead to the development of vaginal dysbiosis and asymptomatic vaginitis. Interestingly, the ascending vaginitis can destroy the cervical fetal membrane through upregulating activation of matrix metalloproteinase-9 (MMP9), an enzyme involved in the remodeling of the fetal membranes and the cervix before the onset of labor, result in a weaken fetal membranes [51] and thus increase the risk of PROM during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…All of the metabolite changes discussed above may work together to impair the healthy vaginal microecology and lead to the development of vaginal dysbiosis and asymptomatic vaginitis. Interestingly, the ascending vaginitis can destroy the cervical fetal membrane through upregulating activation of matrix metalloproteinase-9 (MMP9), an enzyme involved in the remodeling of the fetal membranes and the cervix before the onset of labor, result in a weaken fetal membranes [51] and thus increase the risk of PROM during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prothrombin production can be stimulated by Ureaplasma parvum exposure in fetal membranes. These findings represent a potential novel underlying mechanism of U. parvum ‐induced P‐PROM and the potential use of prothrombin as a predictor of this unfavorable event …”
Section: Prediction Of P‐prom and P‐prom/preterm Delivery Latencymentioning
confidence: 84%
“…These findings represent a potential novel underlying mechanism of U. parvum-induced P-PROM and the potential use of prothrombin as a predictor of this unfavorable event. 56 Timing of delivery is often unknown; approximately half of women who are admitted to hospital with threatened preterm birth remain undelivered after 7 days. 57,58 Several other studies have reported increased odds ratios and/or predictive efficiency for preterm birth when two or more biomarkers (sometimes derived from different tissues) are combined compared to single biomarkers alone.…”
Section: Mehra Et Al Demonstrated That a Shorter Transvaginal Cervicalmentioning
confidence: 99%
“…We congratulate Dr Feng et al on their innovative studies demonstrating infection-induced thrombin production in preterm premature rupture of the membranes (PPROM). 1 Are similar results demonstrable in vivo using noncultured tissues, and which comes first: the infection or thrombin production? Or does prior denervation of the lower genital tract promote opportunist infection and a diverse cascade of pathologic changes in preterm labor/ PPROM?…”
Section: Purinergic P2x3 Positive Cells In Amniotic Membranesmentioning
confidence: 94%
“…We appreciate the thoughtful comments of Dr Quinn and colleagues regarding our recent article. 1 In response to their first question, we demonstrated only the results in vitro cell or tissue explants. The cause-effect is an important question; however, our model is not designed to answer a cause-effect relationship but primarily to show how infection can exaggerate a response with thrombin, a known agent that weakens membranes.…”
Section: Replymentioning
confidence: 99%